2021
DOI: 10.3390/brainsci11060711
|View full text |Cite
|
Sign up to set email alerts
|

Low-Intensity Focused Ultrasound-Mediated Attenuation of Acute Seizure Activity Based on EEG Brain Functional Connectivity

Abstract: (1) Background: Ultrasound has been used for noninvasive stimulation and is a promising technique for treating neurological diseases. Epilepsy is a common neurological disorder, that is attributed to uncontrollable abnormal neuronal hyperexcitability. Abnormal synchronized activities can be observed across multiple brain regions during a seizure. (2) Methods: we used low-intensity focused ultrasound (LIFU) to sonicate the brains of epileptic rats, analyzed the EEG functional brain network to explore the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 58 publications
2
23
0
Order By: Relevance
“…One self-developed 32-channel EEG electrode was used to acquire EEG signals. Previous studies have reported on the effectiveness and safety of electrode use [ 47 , 51 ]. The size of the electrode is shown in Figure 3 A.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One self-developed 32-channel EEG electrode was used to acquire EEG signals. Previous studies have reported on the effectiveness and safety of electrode use [ 47 , 51 ]. The size of the electrode is shown in Figure 3 A.…”
Section: Methodsmentioning
confidence: 99%
“…Previous reports have confirmed that ultrasound (US) has an inhibitory effect on epilepsy. In previous studies, we explored the regulation of low-intensity transcranial pulsed ultrasound (LITPU) on epilepsy [ 47 ]. In this study, we used two different modes of ultrasound on kainic acid (KA)-induced epileptic rats in order to uncover the influence of different modes of ultrasound on the epileptic brain network.…”
Section: Introductionmentioning
confidence: 99%
“…They found that tFUS significantly impaired translation of counterfactual choice values into actual behavioral change and changed the activity and connectivity maps of the ACC ( Fouragnan et al, 2019 ). The study of Zhang et al (2021) reported that FUS reduced the network connections of epilepsy circuits and change the structure of the brain network at the whole-brain level. The adjustment effect of tFUS on neural network connection may be the mechanism of its repeated application to improve brain diseases.…”
Section: Evidence For Mechanismsmentioning
confidence: 99%
“…Post-stroke epilepsy, which accounts for almost 50% of newly diagnosed epilepsy in patients with an age greater than 60 years, could lead to the aggravation of the disease state, seriously affect the prognosis, and even endanger life [ 24 ]. However, most antiepileptic drugs that are used to prevent and treat epilepsy have obvious toxic side effects [ 25 ]. Interestingly, ASOL possesses a very low toxicity and minimal side effects.…”
Section: Resultsmentioning
confidence: 99%